2005
DOI: 10.1109/tcapt.2005.848538
|View full text |Cite
|
Sign up to set email alerts
|

Determination of thermal compact model via evolutionary genetic optimization method

Abstract: Genetic Algorithms (GA) are adaptive search algorithms based on the theory of natural selection and survival of the fittest. In this study, GA was used to derive a thermal compact model of a micro lead frame package. The GA derived model was then used to compute the junction temperature ( ) of the package for various boundary conditions. The results obtained were checked against simulation results of a detailed thermal model and were found to be within 1 5% of error. Computational time taken by the detailed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The feasibility of applying a stochastic search algorithms was studied to derive a steady-state CTM by several authors [7][8][9], which demonstrate the high capabilities of Genetic Algorithms for optimization.…”
Section: Concurrent Model Reduction Approachesmentioning
confidence: 99%
“…The feasibility of applying a stochastic search algorithms was studied to derive a steady-state CTM by several authors [7][8][9], which demonstrate the high capabilities of Genetic Algorithms for optimization.…”
Section: Concurrent Model Reduction Approachesmentioning
confidence: 99%
“…Readers who are interested in the application of genetic algorithms and neural networks to result in compact thermal models may consult Koyamada et al, 17 Aranyosi et al, 18 Clarksean et al, 19 Arunasalam et al 20 and Mallet et al 21 See also the next subsection. …”
Section: Other Approaches Discussed In Literaturementioning
confidence: 99%
“…In general, the 5R star (with optimized area ratios) performs much better than the 3R star. Furthermore, the 5R star scores much worse than the 7R non-star model (a factor [10][11][12][13][14][15][16][17][18][19][20], even for the subsets. Despite this, the data show that the 5R star gives acceptable maximum errors for the junction temperature in the order of 10%, provided we limit the field of application to, e.g., free or forced convection only.…”
Section: "38" and "99" Sets Reduced Sets And Subsets Dotcomp Tqfpmentioning
confidence: 99%
“…GA has been widely used for optimization purposes in microelectronic problems as shown in previous works by Man et al . [ 25 ], Arunasalam et al [ 26 ] and Jeevan et al [ 27 ], while a more detailed description of GA can be found texts written by Goldberg [ 24 ], Mitchell [ 28 ] and Houck et al [ 29 ].…”
Section: Introductionmentioning
confidence: 99%